Literature Review: Fabrication Method, Characterization, Performance, and Application of Cassava Peel as Bio-Coagulant for Wastewater Treatment - Yustika Desti Yolanda; Mia Widyaningsih; Risti Ragadhita; Asep Bayu Dani Nandiyanto (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2022)
The purpose of this study was to conduct a literature review to determine the understanding of current research on the use of Cassava Peel (CP) in the field of wastewater treatment, especially as a coagulant. This study reports on the types of coagulant modification of CP, coagulants characterization of CP for each modification, coagulants performance of CP under various conditions, and various applications of CP coagulant for wastewater treatment. This literature study takes references from 51 articles from the period 2011-2022. We mapped each article used and visualized it using the VOS viewer to find out the relationship between topics and absorption capacity in terms of article titles and keywords. From the results of a literature review study, CP is an attractive option and has the potential to be used as a natural coagulant or adsorbent to remove pollutants (such as dyes and turbidity) in wastewater treatment. The results of this study are expected to provide benefits and ideas for utilizing agricultural waste such as CP to become an economically efficient material. Keywords: Adsorbent, Agricultural waste, Cassava peel, Economical coagulant, VOS viewer, Water treatment.